Negligible exposure to nifurtimox through breast milk during maternal treatment for Chagas Disease - Moroni, Samanta (2019)
Background treatment with nifurtimox (NF) for Chagas disease is discouraged during breast-feeding because no information on NF transfer into breast milk is available. NF is safe and effective for paediatric and adult Chagas disease. We evaluated the degree of NF transfer into breast milk in lactating women with Chagas disease. Patients and methods Prospective study of a cohort of lactating women with Chagas disease. Patients were treated with NF for 1 month. NF was measured in plasma and milk by high performance liquid chromatography (HPLC). Breastfed infants were evaluated at admission, 7th and 30th day of treatment (and monthly thereafter, for 6 months). Results Lactating women with chronic Chagas disease (N = 10) were enrolled (median age 28 years, range 17-36). Median NF dose was 9.75 mg/kg/day three times a day (TID). Six mothers had mild adverse drug reactions (ADRs), but no ADRs were observed in any of the breastfed infants. No interruption of breastfeeding was observed. Median NF concentrations were 2.15 mg/L (Inter quartil range (IQR) 1.32-4.55) in milk and 0.30 mg/L (IQR 0.20-0.95) in plasma. Median NF milk/plasma ratio was 16 (range 8.75-30.25). Median relative infant NF dose (assuming a daily breastmilk intake of 150 mL/ kg/day) was 6.7% of the maternal dose/kg/day (IQR 2.35-7.19%). Conclusions The low concentrations of NF in breast milk and the normal clinical evaluation of the breastfed babies imply that maternal NF treatment for Chagas disease during breastfeeding is unlikely to lead to clinically relevant exposures in the breastfed infants.